Simulating Interactive Learning Scenarios with Intelligent Pedagogical Agents in a Virtual World through BDI-Based Agents - Soliman, M.; Guetl, Christian (Kassel University Press GmbH, 2013)
Intelligent Pedagogical Agents (IPAs) are designed for pedagogical purposes to support learning in 3D virtual learning environments. Several benefits of IPAs have been found adding to support learning effectiveness. Pedagogical agents can be thought of as a central point of interaction between the learner and the learning environment. And hence, the intelligent behavior and functional richness of pedagogical agents have the potential to reward back into increased engagement and learning effectiveness. However, the realization of those agents remains to be a challenge based on intelligent agents in virtual worlds. This paper reports the challenging reasons and most importantly an approach for simplification. A simulation based on BDI agents is introduced opening the road for several extensions and experimentation before implementation of IPAs in a virtual world can take place. The simulation provides a proof-of concept based on three intelligent agents to represent an IPA, a learner, and learning object implemented in JACK and Jadex intelligent agent platforms. To that end, the paper exhibits the difficulties, resolutions, and decisions made when designing and implementing the learning scenario in both domains of the virtual world and the agent-based simulation while comparing the two agent platforms.